Modification of CdTe thin films by Zn reactive diffusion - Dzhafarov, TD; Ongul, F (IOP Publishing Ltd, 2005)
Formation of Cd1-xZnxTe (CdZnTe) ternary compounds as a result of Zn diffusion in CdTe thin films, the structural and optical properties of CdZnTe compounds and I-V characteristics of CdZnTe/CdTe heterojunctions are presented. X-ray diffraction study of Zn/CdTe structures exposed to thermal annealing indicates the formation of CdZnTe compounds. Analysis of the absorption spectra of Zn/CdTe structures, annealed at 500 degrees C, and CdTe thin films show that the energy band gap of the former (1.65 eV) is larger than that of the latter (1.50 eV). Such an increase of the band gap of annealed two-layer Zn/CdTe is attributed to the reactive diffusion of Zn in CdTe films accompanied by the formation of Cd1-xZnxTe compounds with an average value of x = 0.22. The temperature dependence of the effective diffusion coefficient of Zn in CdTe at 430 - 520 degrees C is described as D = 2.5 x 10(-3) exp(-1.30 kT(-1)) cm(2) s(-1).
Keywords: Physics